(3bUI GdbWH GdQHGfi (B( (3SjOi (B) (3CMeO GdHOhis ((3YeQ Hf YKeGf GdQCS Yjf GdeGQOGfi GdMdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdLfI OGQ GdeJbjf s
(3BNQgG (B:s
(3hPcQ Yfg Cfg bGd CeQJ HGdSchJ acGf dGjJcde EdG bdjdkG QVi Gddg Yfg hYf LejY GdChdjGA hYHGO Gddg GdUGdMjf hUdi Gddg Ydi SjOfG eMeO s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B234 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs